Informality and pension reforms in Bolivia: The case of Renta Dignidad - Carla Canelas; Miguel Ni\~no-Zarazúa (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
How social protection programmes affect work choices is a question that has been at the centre of labour economics research for decades. More recently, a scant literature has focused on the effects of social protection on work choices and informal employment in the context of low- and middle-income countries. This paper contributes to this scant literature by examining the effect of Bolivia's Renta Dignidad, a universal non-contributory old-age pension that covers all Bolivians aged 60 years and older. We exploit the discontinuity introduced by the age eligibility criteria and the timing of the announcement of the programme to implement a difference-indifferences approach. Overall, we find that Renta Dignidad has no detrimental effects on labour force participation and the intensity of labour of adult members of beneficiary households. Instead, we find that the pension reduces the intensity of work for girls aged 12-18 living with a pensioner, which indicates a positive effect on intra-household time allocation. In terms of work choices, Renta Dignidad reduces the probability of holding a salaried job in rural areas by about 8 percentage points, which denotes a shift from formal to informal employment.
Keywords: J08; J26; I38; 330; social protection; informal employment; Bolivia; Renta Dignidad; non-contributory oldage pension